A lane detection approach based on intelligent vision. (February 2015) - Yi, Shu-Chung; Chen, Yeong-Chin; Chang, Ching-Haur
Abstract: This paper proposes driver assistant system architecture based on image processing techniques. A camera is mounted on the vehicle front window to detect the road lane markings and determine the vehicle's position with respect to the lane lines. A modified approach is proposed to accelerate the HT process in a computationally efficient manner, thereby making it suitable for real-time lane detection. The acquired image sequences are analyzed and processed by the proposed system, which automatically detects the lane lines. The experimental results show that the system works successfully for lane line detection and lane departure prediction.